2023
DOI: 10.1111/jvim.16635
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac troponin I as a predictor of death in critically ill cats

Abstract: Background Abnormally high serum cardiac troponin I (cTnI) concentration, reflecting leakage from or necrosis of cardiomyocytes, is a negative prognosticator for death in dogs. Objectives To investigate in critically ill cats whether serum cTnI concentration is abnormally high, identify conditions associated with abnormally high cTnI concentrations, and evaluate cTnI as an independent prognosticator for death and a potential coprognosticator to the acute patient physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In veterinary medicine, a high serum concentration of cTnI is reported as a negative prognostic marker of death in dogs affected with SIRS [ 42 , 43 , 44 ]. Significantly higher levels of cTnI have been assayed also in cats with hypertrophic cardiomyopathy [ 45 , 46 , 47 ] and no specific primary cardiac diseases such as hyperthyroidism [ 48 ], renal disease [ 23 ], critical illness [ 48 , 49 ], and hypertension [ 50 ]. This study showed that an increase in cTnI suggesting the presence of myocardial injury is common in cats affected with SIRS, similarly to dogs [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, a high serum concentration of cTnI is reported as a negative prognostic marker of death in dogs affected with SIRS [ 42 , 43 , 44 ]. Significantly higher levels of cTnI have been assayed also in cats with hypertrophic cardiomyopathy [ 45 , 46 , 47 ] and no specific primary cardiac diseases such as hyperthyroidism [ 48 ], renal disease [ 23 ], critical illness [ 48 , 49 ], and hypertension [ 50 ]. This study showed that an increase in cTnI suggesting the presence of myocardial injury is common in cats affected with SIRS, similarly to dogs [ 51 ].…”
Section: Discussionmentioning
confidence: 99%